From Reading Comprehension to Critical Literacy: Adapting Huh's Model in Online Indonesian EFL Classrooms - Dian Resty Pratiwi Ahmad; Utami Widiati; Ekaning Dewanti Laksmi; Siti Muniroh; Dewi Masitho Istiqomah (CV FOUNDAE, 2026)
ritical literacy has become an essential component of English as a Foreign Language (EFL) reading instruction, yet its implementation remains challenging in online learning environments where students often struggle to move beyond literal comprehension toward critical engagement with texts. Although Huh’s instructional model provides a structured framework for developing critical literacy, evidence regarding its adaptation to online EFL contexts remains limited. This study investigated how an adapted version of Huh’s model supported the development of reading comprehension and critical literacy in an online Indonesian EFL classroom. Employing collaborative classroom action research, the study involved 21 undergraduate students across three iterative instructional cycles. Data were collected through reading assessments, students’ digital artifacts, and structured online classroom observations, and analyzed using descriptive statistics alongside Miles and Huberman’s interactive qualitative analysis. The findings indicate that the adapted model progressively strengthened students’ reading comprehension and critical literacy by integrating scaffolded learning activities, explicit instruction in critical literacy concepts, locally relevant sociopolitical texts, and student-generated critical questioning. The iterative refinement of instructional practices also encouraged students to engage more critically with multiple perspectives and develop evidence-based responses to authentic social issues. This study extends Huh’s framework by demonstrating how context-sensitive pedagogical adaptations can effectively support critical literacy development in online EFL settings. The findings offer practical guidance for designing online reading instruction that integrates critical pedagogy with meaningful local contexts while fostering students’ critical engagement with contemporary societal issues.